FAKTOR-FAKTOR YANG MEMPENGARUHI KEINGINAN MAHASISWA UNTUK BERWIRAUSAHA (Studi pada Mahasiswa S1 Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Brawijaya) - Rani Satiti; Wiwik Hidajah Ekowati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The purpose of this study was to find out how much a student of the Department of Accounting FEB UB who wish to become entrepreneurs and the factors that served as impetus to the desire of students to entrepreneurship. The number of samples 218 student obtained from the calculation formula Slovin. The method used is quantitative method primary data source in the form of a questionnaire. The analytical tool used was Partial Least Square (PLS) program through SmartPLS. Of the total questionnaires distributed is known that 96% Accounting Department FEB UB students have a desire for entrepreneurship. The results of the collection and processing of data showed that of the five independent variables, three of which are successful in entrepreneurship (X1), tolerance to risk (X2), the freedom to work (X3) proved positive effect on the student desire for entrepreneurship (Y). Meanwhile, two other variables, namely entrepreneurship education (X4) and parental employment background differences (X5) had no effect on student wishes to entrepreneurship (Y). In the calculation results of R-square showed a score of 0.6774. The score is explained that the dependent variable in this study is the desire of students to entrepreneurship by 67% is explained by the independent variables in the success of entrepreneurship, tolerance of risk, freedom in work, entrepreneurship education, and parental employment background differences. While the remaining 33% is explained by other variables outside the research model. Keywords: Entrepreneurship, successful in entrepreneurship, tolerance to risk, freedom to work, entrepreneurship education, parental employment background differences, student wishes to entrepreneurship.